Transforming cassava peels into animal feed - International Potato Center; International Livestock Research Institute; International Institute of Tropical Agriculture (International Livestock Research Institute, 2015)
This video explains how cassava peels can be dried and converted into animal feed - reducing environmental waste, feeding animals and providing livelihoods